Economic Bubbles and Startup Lifecycle: Case Study of Tanihub’s Rise and Fall - Maulana Firmansyah, Akbar; Umais Al Ayyubi, Waridad (Blantika: Multidisciplinary Journal, 2025)
The growth of startups in Indonesia, especially in the agribusiness sector, has experienced significant dynamics in recent years. TaniHub, as one of the leading startups, has experienced a journey that mirrors the economic bubble phenomenon, from a rapid rise to a sharp decline. This study aims to analyze TaniHub's life cycle through the economic bubble theory, to understand how this theory can be applied to private startups and provide insights into the development of a new life cycle concept in the context of an emerging market. A qualitative approach was used with a case study method, analyzing TaniHub's journey from its founding in 2016 to its collapse in 2023. Data were collected from secondary sources, including media reports and official documents, and analyzed using the economic bubble theory framework. The results of the analysis show that TaniHub's journey through five phases of the economic bubble displacement, boom, euphoria, financial distress, and revolution reveals how overinvestment and unrealistic expectations contributed to the company's failure despite having significant funding. The study concludes that although TaniHub managed to attract large investments, the lack of sustainability in its business model and ineffective growth management led to its rapid decline. These findings provide valuable insights for stakeholders in the startup sector to understand the risks of rapid growth and the importance of careful management in avoiding economic bubbles.